2020
DOI: 10.1016/j.indmarman.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

We survived this! What managers could learn from SMEs who successfully navigated the Greek economic crisis

Abstract: Small and medium size enterprises in both business to business and consumer markets are particularly vulnerable to economic downturns. Concentrating on the Greek economic crisis, one of the toughest and most prolonged on a global scale, the present research sheds light on both anthropocentric and business-centric factors that helped SMEs survive, therefore, providing a valuable survival manual. Per findings of two studies performed under the given economically intense conditions, it is evidenced that the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 112 publications
3
74
0
13
Order By: Relevance
“…Training should be conducted so everyone is adaptive and can modify their needs as per requirements. Kottika et al, 2020 Impact on SMEs involving business and consumer markets There has been economic breakdown in the growth of United States GDP as it decreased by 4.8% in the first quarter of 2020. In European nations, GDP shrunk by 3.8% in the same period It is important to develop entrepreneurial personality traits as it is clearly shown that their attitude plays a significant role in the orientation of SMEs.…”
Section: (Continued)mentioning
confidence: 99%
“…Training should be conducted so everyone is adaptive and can modify their needs as per requirements. Kottika et al, 2020 Impact on SMEs involving business and consumer markets There has been economic breakdown in the growth of United States GDP as it decreased by 4.8% in the first quarter of 2020. In European nations, GDP shrunk by 3.8% in the same period It is important to develop entrepreneurial personality traits as it is clearly shown that their attitude plays a significant role in the orientation of SMEs.…”
Section: (Continued)mentioning
confidence: 99%
“…2,14 The smaller the organization, the closer the decision-makers are to their customers and other stakeholders facilitating helpful market information to a better focus. 2,12,14 In the wake of COVID-19, Ecuadorian government have issued a mandatory lockdown. SMEs, a critical part of the Ecuador economy, are scrambling to stay afloat, but also are under extreme duress feeling the economic strain amid COVID-19; a lot of them are folding up.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During a crisis, not only the performance of the business is at stake, but its survival and the findings verified that a good management and a market orientation have positive impact on SMEs' performance in times of crisis. 12 Labeled as a black swan event, COVID -19 present the fears of disappearance of many SMEs, times like these call for clarify priorities that will allow return to a new normal with less possible harm. In such environments, SMEs have to re-adjust and improve their strategies and behaviors fit to the environment in order to ensure business survival.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the data of 250 SMEs from Greece, Kottika et al (2020) suggest that, despite unfavourable conditions, 85% of SMEs survived the pandemic by focusing on productivity, e ciency, downsizing, and new partnerships with suppliers. Within the existing body of research on the impact of the pandemic on small businesses, the question of how corporate environmental performance informs the survival of small businesses during the crisis has been neglected.…”
Section: Impact Of the Covid-19 Pandemic On The Msme Sectormentioning
confidence: 99%